Analisis Pemikiran Al-Fārābī tentang Kesejahteraan Sosial dan Relevansinya terhadap Pembangunan Ekonomi - Amelia Nurasiah; Husnul Kholifah Nur Inayah; Rizka Anggriani; Lina Marlina; Ana Fauziya Diyana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the concept of social welfare in the thought of Al-Farabi and its relevance to economic development. Al-Farabi explains that the main goal of social life is to achieve happiness (al-sa‘ādah), which is not only related to material welfare but also includes moral, intellectual, and spiritual values. This research uses a qualitative method with a library research approach by analyzing the works of Al-Farabi and various relevant scientific literatures. The results show that the concept of social welfare according to Al-Farabi is based on four main principles: social happiness, social justice, community cooperation, and the role of morality and education. These principles indicate that social welfare is not only dependent on economic aspects but also on ethical values, wise leadership, and social cooperation within society. Furthermore, Al-Farabi’s thought is also relevant to modern economic development, particularly in terms of distributive justice, moral-based development, and the role of the state in achieving public welfare.